No Difference in Functional Outcomes after Total Knee Arthroplasty with or without Pinless Navigation - Zhu, Meng; Chen, Jerry Yongqiang; Chong, Hwei Chi; Pang, Hee Nee; Tay, Darren Keng Jin; Chia, Shi-Lu; Lo, Ngai Nung; Yeo, Seng Jin (The Journal of Knee Surgery, 2018)
This study aims to investigate the functional outcomes of pinless navigation (BrainLAB VectorVision Knee 2.5 navigation system; Munich, Germany) as an intraoperative alignment guide in total knee arthroplasty (TKA). A prospective, 24-month follow-up study of 100 patients who were scheduled and randomized into two groups, the pinless navigation and conventional surgery, was conducted. All TKAs were performed with the surgical aim of achieving neutral coronal alignment with the 180-degree mechanical axis. The outcomes measured in this study were Oxford Knee Score (OKS), Knee Society Score (KSS), Short Form-36 (SF-36), and range of motion (ROM). At 24-month postoperatively, four and two patients were lost to follow-up from the pinless navigation group and conventional group, respectively. There were no significant differences in absolute scores of the OKS, KSS, and ROM, as well as changes from preoperative baseline, between pinless navigation and conventional groups at both 6 and 24 months postoperatively. Pinless navigation results in comparable functional outcomes as conventional TKA at 6 and 24 months postoperatively.
Keywords: total knee arthroplasty; computer-assisted surgery; pinless navigation; functional outcomes